Genetic Engineering - An Insight Into the Strategies and Applications 2016
DOI: 10.5772/66717
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Modification of Stem Cells in Diabetes and Obesity

Abstract: Genetic modification, or gene transfer, represents a method of treatment for several diseases. It has been used extensively in the context of cardiovascular diseases; however, its role in the context of metabolic diseases, such as diabetes and obesity, has remained largely unexplored. In this chapter, we will review the use of adult stem cells, focusing on endothelial progenitor cells (EPCs) and mesenchymal stromal cells (MSCs), in the context of diabetes. We have highlighted the use of viral vectors, particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…To solve this problem, we used short‐term silencing of p53 where the viral construct would not be viable beyond 28 days. Effects of adenoviral silencing usually persist ≈28 days . This time span is perfect because the time required by EPCs to transform to a mature endothelium is also ≈28 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To solve this problem, we used short‐term silencing of p53 where the viral construct would not be viable beyond 28 days. Effects of adenoviral silencing usually persist ≈28 days . This time span is perfect because the time required by EPCs to transform to a mature endothelium is also ≈28 days.…”
Section: Discussionmentioning
confidence: 99%
“…This time span is perfect because the time required by EPCs to transform to a mature endothelium is also ≈28 days. Simultaneously, we did not want to use a turn‐on, turn‐off gene promoter, with another DNA virus like adeno‐associated virus, as the effect of silencing could be considered as “leaky.” Thus, the use of an adenovirus as a gene modification vector was the best selection, with a transduction efficacy profile better than liposomes …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been many different markers of inflammation used to look at endothelial dysfunction, cell-based biomarker such as hematopoietic progenitor cells CD34+ cells to assess endothelial function and treat cardiovascular diseases [812] has been widely used in various clinical scenarios [10]. Peripheral blood- and bone marrow-derived hematopoietic CD34+ cells are deemed to be premature or progenitor cells where CD34 is a progenitor marker.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have described a reduction in EPCs in that population, whereas others have shown an increase or no changes in the number of EPCs in OSA [18]. Despite the fact that many studies on EPCs in OSA have been reported, results are still controversial as definition of EPCs without a cell surface marker can be confusing [10]. In OSA patients, a reduction in circulating CD34+ cells can occur, where CD34+ cells may succumb to apoptosis secondary to increased level of reactive oxygen species (ROS) presence.…”
Section: Introductionmentioning
confidence: 99%